Culture Representations Incorporated within the English Textbook Used for Teaching Seventh-Grade Students in Indonesia - Astrid, Annisa; Saputra, Eko; Sukma, Fitri Alya Okta; Chairuman, Muhamad Chalik (Journal of English Education and Teaching, 2023)
This study aims to examine the cultural representation incorporated within the English textbook that the teachers utilized for instructing seventh-grade students in Indonesia. The Study employed qualitative content analysis techniques. The study utilized documentation and a checklist table containing criteria to assess the presence of cultural aspects in the textbook recommended by experts in teaching English as a foreign language. The results indicated that the textbook has successfully fulfilled specific criteria for including cultural information. A distinct and well-defined learning objective accompanies every chapter within this English textbook. The textbook organizes its content into individual chapters, each exploring diverse topics about various cultural aspects. The introduction of vocabulary on the topic of each unit occurs exclusively within the respective unit, without subsequent repetition in subsequent chapters. The content covered in Chapters 1 to 5 of the textbook has encompassed a wide range of cultural elements, exhibiting significant diversity. The material has been tailored to suit the student's age group. Every chapter within this English textbook also presents four distinct categories of language skills. However, the learning materials primarily emphasize Indonesian culture through the inclusion of cultural materials. The chapters within the textbook need to cultivate students' awareness of intercultural understanding. There need to be more activities that facilitate students' engagement in intercultural understanding and cross-cultural communication